Does CFPB oversight crimp credit? - Andreas Fuster; Matthew Plosser; James Vickery (Federal Reserve Bank of New York, 2018)
We study the effects of regulatory oversight by the Consumer Financial Protection Bureau (CFPB) on credit supply as well as bank risk-taking, growth, and operating costs. We use a difference-in-differences approach, making use of the fact that banks below a 10 billion size cutoff are exempt from CFPB supervision and enforcement activities. We find little evidence that CFPB oversight significantly reduces the overall volume of mortgage lending. However, we find some evidence of changes in the composition of lending-CFPB-supervised banks originated fewer loans to risky borrowers, offset by an increase in large "jumbo" mortgages. We find no clear evidence of substitution in lending between bank and nonbank subsidiaries, or effects on asset growth or bank noninterest expenses.
Keywords: D18; G21; G28; 330; consumer financial protection bureau; credit; mortgage; regulation